The Relationship Between Learning Climate And The Learning Motivation Of Trainees At Smart College Training And Training Institutions In The City Of Padang - Rahma, Yulia; Wisroni, Wisroni (Universitas Negeri Padang, 2025)
The background is the low motivation of automotive trainees to learn. The purpose of this study is to gain an understanding of the learning climate of automotive training, as well as a picture of the learning motivation of automotive training participants, and to examine the relationship between the learning climate and the learning motivation of automotive training participants at LKP Smart College Kota Padang. This study took a quantitative approach to correlational research. The participants in this study were 18 trainees who attended automotive training at LKP Smart College Kota Padang. In this study, the sample size was 14 participants drawn from 80% of the population, for a total of 18 people. The data collection technique used is a questionnaire, and the data analysis technique uses a percentage formula and a ranking order correlation formula. The results of this study show that (1) the learning climate for automotive training is classified as less conducive, (2) the learning motivation of automotive training participants is low, and (3) there is a relationship between the learning climate and learning motivation which is stated to be significant because this is classified as really high. It is essential that instructors pay attention to participant variety so that participants feel appreciated and driven to further develop their talents. It is essential that training organizers provide suitable facilities in order to establish a comfortable learning environment and boost participants' learning motivation. It is also recommended that learners boost their motivation to learn. Keywords: Learning climate, learning motivation